CTA Project Completion Report: Brussels Briefings - Ajong, Félix; Chavez-Tafur, Jorge (Technical Centre for Agricultural and Rural Cooperation, 2020)
Organised by CTA, the European Commission (EC), the African, Caribbean and Pacific (ACP) Group of States and Concord, the Brussels Development Policy Briefings have been a flagship initiative providing an inclusive policy dialogue forum for 13 years, focusing on the most critical issues facing agriculture and rural development in Africa, the Caribbean and the Pacific countries. The Briefings offered a structured mechanism for the exchange of information and experience among representatives of the development community in Brussels. This was meant to help all these experts communicate with each other, and help increase the collaboration and partnership options. Many of the world’s leading experts were involved in 60 high-level policy dialogue meetings since the Brussels Development Policy Briefings were launched in 2007. Supporting a network of Brussels-based policy-makers and development practitioners, especially those focusing on rural development issues, the meetings provided the basis for new partnerships and helped many initiatives to scale up. As recognised by Leonard Mizzi, Head of Unit at the EC, Directorate-General for International Cooperation and Development, the Brussels Briefings were popular and influential “in providing the cutting-edge latest information on topical issues, the policy debates [were] embedded in the highest echelons of the ACP constituency and [went] well beyond the event.”